A Comparative Study of Nigeria Economic Growth between 2001/ 2020 and 1981/2000 - Owan Raphael Asu; Ojekudo Nathaniel (Research Parks Publishers, 2023)
The study examines a comparative study of two quarters of the Nigerian economy, 2001/2020 and 1981/2000. Identifies the problems facing Nigeria. A multiple linear regression model was used for the analysis. The data for the analysis was obtained from Nigeria's GDP 1981-2020/Macro Trends a publication from the Central Bank of Nigeria and the National Bureau of Statistics. The results show that the first quarter of 2001/2020 has the least root mean square error and the inequality coefficient values of 3.57 and 0.15 denoting the best model. This means that the first quarter (2001/2020) connotes the best economic growth in Nigeria.